G187(P) Training together to improve paediatric palliative care through interprofessional simulation. (25th October 2020) - Balendran, G; Vitello, S; Sancroft, N; Gilroy, F; Kirk, S; Kilonback, A
Abstract : Aim: Although there are rising numbers of children with life-limiting diseases in the UK, there is a paucity of postgraduate paediatric palliative care training for both doctors and nurses. Current resources tend to focus on symptom management rather than the challenges of undertaking difficult conversations with patients and families. Interprofessional simulation-based education has been shown to improve both technical and human factor skills. We aimed to design an innovative interprofessional simulation-based course to improve confidence with paediatric palliative care. Method: The course was designed and delivered by an interprofessional faculty. Four scenarios were designed using a high-fidelity manikin and professional actress, focusing on key palliative care themes: advanced care planning, recognition of the dying patient, autonomy and care after death. The diamond debrief model was used to explore technical and human factor skills with a focus on real-life application. We also included a symptom management workshop. Pre-and post-course questionnaires using Likert scales 0 to 100, (where 0 = not at all and 100 = totally agree) and free-text comments were completed by all participants to evaluate Kirkpatrick Levels one and two. Results: There were nine participants including paediatric consultants, paediatric registrars, senior paediatric nurses and oncology nurse specialists. Feedback showed increases in average confidence levels. There was a 40-point (41 to 81) increase in confidence with having discussions surrounding dying, a 27-point (51 to 78) increase in confidence with DNAR discussions, and a 33-point (46–79) and 30-point (51–81) increase in confidence with assessing and managing patients at the end of life respectively. Highly positive feedback was received regarding the fidelity of the scenarios (91), the opportunity to practice clinical skills (83) and the usefulness of the feedback from the debrief sessions (93). All of this was supported by qualitative data from free-text comments. Conclusion: This course is unique to our paediatric training region. Our feedback has shown that paediatric palliative care is an area in which many healthcare professionals lack confidence. We recommend interprofessional simulation training as an effective way of improving knowledge, confidence and non-technical skills essential for delivering paediatric palliative care to patients and their families.